Draft Annual Plan 1990-91 Government of Uttar Pradesh - Planning Commission (Planning Commission, 1990)
Agriculture and Allied Activities, Rural Development, Special Area Programmes, Irrigation and Flood Control, Industry and Minerals, Transport, Science, Technology and Environment, General Economic Services, Civil Aviation, Roads and Bridges
Secretary to Government of Uttar Pradesh, Planning Department, Lucknow
Government of India Planning Commission
Keywords: Agriculture and Allied Activities; Rural Development; Special Area Programmes; Industry and Minerals; Transport; Science; Technology and Environment; General Economic Services; Civil Aviation; Roads and Bridges; Irrigation and Flood Control